2005
DOI: 10.1002/jcp.20493
|View full text |Cite
|
Sign up to set email alerts
|

Cartducin, a paralog of Acrp30/adiponectin, is induced during chondrogenic differentiation and promotes proliferation of chondrogenic precursors and chondrocytes

Abstract: We previously reported that CORS26 gene, isolated from C3H10T1/2 cells treated with transforming growth factor-beta1, was predominantly expressed in cartilage. Because the gene product is a kind of secretory protein produced by cartilage tissue, we named it "cartducin". Cartducin shares a similar modular organization to adipocyte-derived hormone, adiponectin. In this study, we investigated cartducin function during chondrogenesis and cartilage development. In situ hybridization analysis showed that cartducin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 33 publications
4
82
0
Order By: Relevance
“…The defining feature of CTRPs is the presence of the signature "C1q/TNF-like" globular domain located at the C terminus, which is homologous to the immune complement C1q and structurally resembles that of TNF-␣ (9). Functional studies thus far have indicated significant roles for CTRPs in the endocrine (4 -8, 10, 11), immune (12), vascular (13,14), skeletal (15), and sensory systems (16 -18).…”
mentioning
confidence: 99%
“…The defining feature of CTRPs is the presence of the signature "C1q/TNF-like" globular domain located at the C terminus, which is homologous to the immune complement C1q and structurally resembles that of TNF-␣ (9). Functional studies thus far have indicated significant roles for CTRPs in the endocrine (4 -8, 10, 11), immune (12), vascular (13,14), skeletal (15), and sensory systems (16 -18).…”
mentioning
confidence: 99%
“…C1QTNF1, which is expressed by vascular smooth muscle cells, inhibits collagen-induced platelet aggregation (9) and activates Akt and MAPK (10). C1QTNF3 is expressed by chondrocytes, and recombinant C1QTNF3 stimulates cartilage development by activating extracellular signalregulated kinase (ERK) and Akt signaling pathway (11,12). Recently, it was reported that C1QTNF2 induces the phosphorylation of AMPK in C2C12 myocytes, resulting in increased glycogen accumulation and fatty acid oxidation (6).…”
mentioning
confidence: 99%
“…Whereas adiponectin is exclusively expressed by adipocytes, CORS-26 mRNA is also detected in cartilage, kidney, colon, small intestine, placenta, lung, spleen, fibroblasts, human monocytic and dendritic cells 5,6 . In addition, strong CORS-26 mRNA expression has been found in osteosarcoma, chondroblastoma and giant cell tumors 2,3,6 .…”
Section: Cors-26 Expressionmentioning
confidence: 99%
“…CORS-26 has been shown to be a novel growth factor that plays an important role in regulating both chondrogenesis and cartilage development (CORS-26 gene is predominantly expressed in growth plate cartilage) 5,8 . Skeletal development requires condensation of multipotential mesenchymal cells in order to differentiate into various cell types.…”
Section: Cors-26 Effect On Chondrogenesis and Cartilage Developmentmentioning
confidence: 99%
See 1 more Smart Citation